1977
DOI: 10.3758/bf03209590
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of stimulus-reinforcer associations established with multiple schedules

Abstract: Multiple schedules established stimulus-reinforcer IS-SR) associations on baselines in which equal response rates and patterning were maintained in all components. Subsequently, stimuli associated with an increase in reinforcement but no change in ongoing response rate were compounded. For one experimental group, free-operant avoidance WOA) was programmed in tone and in light while variable-Interval (VI) food reinforcement was effective in their simultaneous absence irr + L). The opposite stirnulus-schedule co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The significant test differences between control and transfer groups of this experiment, systematically replicated in Experiment 2, reveal the power of the manipulated variables, and stand on their merits. Weiss (1977) did report some results potentially relevant to a concern about the unconditioned disruptive powers of the compound. He gave rats extensive training in which FOA operated in tone, light and 'F +L.…”
Section: Resultsmentioning
confidence: 99%
“…The significant test differences between control and transfer groups of this experiment, systematically replicated in Experiment 2, reveal the power of the manipulated variables, and stand on their merits. Weiss (1977) did report some results potentially relevant to a concern about the unconditioned disruptive powers of the compound. He gave rats extensive training in which FOA operated in tone, light and 'F +L.…”
Section: Resultsmentioning
confidence: 99%
“…Spence's theory made no distinction between gradients resulting from operant or respondent contingencies. Therefore, because excitatory and inhibitory gradients for autoshaped pecks following interdimensional discrimination training have been reported (Tomie et al, 1976;Wessells, 1973) Although Spence (1937) made no distinction between operant and respondent control here, Weiss' (1971Weiss' ( , 1977Weiss' ( , 1978 two-factor model of stimulus control deals with the contribution of these different contingencies to the likelihood, and robustness, of peak shift. He observed that in the large majority of operant discrimination studies, the presence of S+ is correlated with an increase in both response and reinforcement frequency and argued that this covariation obscures the contributions of each contingency to the resulting stimulus control.…”
Section: Contingency Assaysmentioning
confidence: 97%
“…109-114). Using appetitive operant conditioning, summation has been found with rats (Hamm, Porter, & Oster, 1978;Strub & Barske, 1977;Weiss, 1977) and pigeons (Long & Allen, 1974;Meltzer & Hamm, 1976). Summation has also been reported with avoidance responding using dogs (LoLordo & Hart, 1972)and rats (Emurian & Weiss, 1972;Van Houten & Rudolph, 1971;Weiss, 1976Weiss, , 1977.…”
mentioning
confidence: 88%